Supplier selection service-case study UTB (2012)
Supplier selection supported by methods based on computational tools are fundamental enterprise actions. This paper proposes the development of supplier selection model supported on a computational tool, using the purchasing department of Universidad Tecnológica de Bolívar as a case study. The review of different decision making techniques, yielded AHP as the most appropiate technique because of its multi-variable and multi-criteria capabilities. The design of the tool is based on Service Oriented Computing, as it allows easier integration, a better and faster response to process change and the environment changing needs. In this work, the design of the selection model, the identification and implementation of the services for selection and evaluation of suppliers were carried out. © 2012 IEEE.